2020
DOI: 10.1039/c9cc06968b
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of polyoxometalate rings on gold nanorods

Abstract: Polyoxometalates (POMs) were self-assembled on cetyltriethylammonium bromide-covered gold nanorods and formed periodic POM rings, which could be used as templates for the synthesis of Ag nano-rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The surface of Au NRs can be automatically coated by small-molecule ligands through electrostatic interaction and π-stacking. , Thiol molecules are prevalent ligands for the generation of a self-assembled monolayer on Au NRs. They include benzenethiol, 3-mercaptopropionic acid, mercaptoethylamine, alkanethiol, , 11-mercaptoundecanoic acid, , 16-mercaptohexanoic acid, and 2-aminoethanethiol .…”
Section: Synthesismentioning
confidence: 99%
“…The surface of Au NRs can be automatically coated by small-molecule ligands through electrostatic interaction and π-stacking. , Thiol molecules are prevalent ligands for the generation of a self-assembled monolayer on Au NRs. They include benzenethiol, 3-mercaptopropionic acid, mercaptoethylamine, alkanethiol, , 11-mercaptoundecanoic acid, , 16-mercaptohexanoic acid, and 2-aminoethanethiol .…”
Section: Synthesismentioning
confidence: 99%
“…S13 †). 31 The dynamic light scattering (DLS) results confirmed that M-AuNRs and M-AuNR@POMs maintained a further improved dispersion in water (Fig. S14 †).…”
Section: Synthesis and Characterization Of The Nir Photothermal Catal...mentioning
confidence: 64%
“…Thus, the combination of POMs with AuNRs could be expected to achieve the property of plasma-enhanced photothermal catalysis. However, the existing reports of POMs and AuNRs composite nanomaterials are limited to the study of their assembly morphology 31 and biological applications, 32 and have not studied their photocatalytic aspects in detail yet.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, microparticles with twisted cylinders of PDMS domains were observed (Figures 2c and S11). In this case, the cationic surfactants will preferentially bind to {Mo 72 V 30 } due to their stronger electrostatic attractions than that of protonated PS-NH 2 , 48 leading to the detachment of PS-NH 2 and the disassembly of NPSs (Figures 2d, S12, and Table S1). Then, PS 5.5k -NH 2 will migrate to the PS microdomains and induce the structure transition.…”
Section: Resultsmentioning
confidence: 99%